Controle da Qualidade da Água do Arroio Portão Portão, RS - NAIME, ROBERTO; FAGUNDES, ROSÂNGELA SCHUCH (Pesquisas em Geociências, 2005)
<!– .p text-align: justify; –> This work presents the environment attendance of Portão River, a river of the hydrographic basin of Rio dos Sinos, Rio Grande do Sul, southern Brazil. The improvement of environmental conditions demands a diagnostic of the actual situation. By this way, it is possible to propose mitigation, compensation and promotion of better quality of life for the populations. Chemical parameters of water were observed during three months, in order to evaluate the environmental conditions, and to promote environmental improvement for this region, in the context of physical, biological and economic conditions.